Design of Muster Area as Earthquake Evacuation Area in North Lombok Regency, West Nusa Tenggara. Issue 1 (May 2020) - Amni, B D H; Hadi, A A; Perdinan,
Abstract: Mitigation of disaster is an effort to decrease the impact of damage caused by natural disasters i.e. earthquakes. West Nusa Tenggara Barat Province (NTB) Indonesia was hit by 7.0 earthquakes in July 2018. Earthquake disaster affects the community to become a traumatic feeling and disease because of the lack of supporting facilities in the mitigation area. The local government of Lombok is preparing reconstruction and rehabilitation including mitigation area. The Green open spaces of the city can be utilized as an evacuation area or muster area in the incident of a natural disaster. Muster areas as disaster mitigation are still rarely found in Indonesia, particularly in North Lombok Regency. The muster area should be placed on the area of potentially occurring natural disasters in the Regency. Infrastructure and network utilities of muster areas must have several sectors, such as the provision of drinking water, electricity, telecommunications panel, accessibility, drainage, sewer system, parking area, and a toilet. However, green open space in North Lombok Regency, particularly in natural disaster-prone areas, is not yet utilized as a muster area. The muster area was designed according to people's needs. The questionnaire method was used to obtain input from North Lombok People who experienced the disaster.